Pathophysiology of polycystic ovary syndrome revisited: Current understanding and perspectives regarding future research - Miyuki Harada (Reproductive Medicine and Biology, 2022)
Abstract Background Polycystic ovary syndrome (PCOS) is the most common endocrine disorder among reproductive‐age women and has lifelong effects on health. Methods In this review, I discuss the pathophysiology of PCOS. First, I summarize our current understanding of the etiology and pathology of PCOS, then, discuss details of two representative environmental factors involved in the pathogenesis of PCOS. Finally, I present perspectives regarding the directions of future research. Main findings The pathophysiology of PCOS is heterogeneous and shaped by the interaction of reproductive dysfunction and metabolic disorders. Hyperandrogenism and insulin resistance exacerbate one another during the development of PCOS, which is also affected by dysfunction of the hypothalamus‐pituitary‐ovarian axis. PCOS is a highly heritable disorder, and exposure to certain environmental factors causes individuals with predisposing genetic factors to develop PCOS. The environmental factors that drive the development of PCOS pathophysiology make a larger contribution than the genetic factors, and may include the intrauterine environment during the prenatal period, the follicular microenvironment, and lifestyle after birth. Conclusion On the basis of this current understanding, three areas are proposed to be subjects for future research, with the ultimate goals of developing therapeutic and preventive strategies and providing appropriate lifelong management, including preconception care.